Sistem Pendukung Keputusan Penetapan Kenaikan Gaji Karyawan dengan Menggunakan Metode Algoritma C4.5 pada PT. Harapan Makmur Surakarta - Dwi Ardiyanto Puro, Andriani KKW, Sri Sri Hariyati Fitriasih (Jurnal Ilmiah SINUS, 2014)
The problem that often occurs in the employee performance appraisal process include the subjectivity of decision-making determination of salary increase, especially if some of the employees who have the ability are not much different from the skills and behavior. The use of decision support systems is the determination of salary increases, expected to reduce subjectivity in the decision whether the employee is entitled to a salary rise or not. In its place will be calculated on education, occupation, personality, number of children and length of employment, so expect its employees to human resources terms comparable to the terms of a pre-determined salary increases companies. Decision support systems salary increase determination is made based on the results of the calculation between education, occupation , personality, number of children and length of employment . The process of data calculation is done to determine whether the employee's salary for a raise or not . Aspects are based on data taken with the scope of employees , value raise, raise and process reports. To overcome these problems , then we will develop an application system of setting employee salary increases using the C4.5 algorithm. Making these applications using Code Gear RAD 2009 with a MySQL database . System design using Schematic Diagram, HIPO, DAD, ERD. The results achieved in the form of employee data, a set of variables, test data and reports which consist of a report of the decision and report employee data . Keywords: C4.5 algorithm, Decision Supporting System, Fixing Employee Salary Increase